Innovative Artificial-Intelligence- Based Approach for the Biodegradation of Feather Keratin by Bacillus paramycoides, and Cytotoxicity of the Resulting Amino Acids - Moussa, Zeiad; Darwish, Doaa B.; Alrdahe, Salma S.; Saber, WesamEldin I. A. (Frontiers in Microbiology, 2021)
The current study reported a new keratinolytic bacterium, which was characterized as Bacillus paramycoides and identified by 16S rRNA, and the sequence was then deposited in the GenBank (MW876249). The bacterium was able to degrade the insoluble chicken feather keratin (CFK) into amino acids (AA) through the keratinase system. The statistical optimization of the biodegradation process into AA was performed based on Plackett-Burman design and rotatable central composite design (RCCD) on a simple solid-state fermentation medium. The optimum conditions were temperature, 37 °C, 0.547 mg KH2PO4, 1.438 mg NH4Cl, and 11.61 days of incubation. Innovatively, the degradation of the CFK process was modeled using the artificial neural network (ANN), which was better than RCCD in modeling the biodegradation process. Differentiation of the AA by HPLC revealed the presence of 14 AA including essential and non-essential ones, proline and aspartic acids were the most dominant. The toxicity test of AA on the HepG2 cell line did not show any negative effect neither on the cell line nor on the morphological alteration. B. paramycoides ZW-5 is a new eco-friendly tool for CFK degradation that could be optimized by ANN. However, additional nutritional trials are encouraged on animal models.